A study of regional variation in the inpatient cost of lower extremity amputation among patients with diabetes in the United States. (June 2013) - Yin, Hongjun; Radican, Larry; Kong, Sheldon X.
Abstract Objective: Understanding of the effects of providers' cost on regional variation in healthcare spending is still very limited. The objective of this study is to assess cross-state and cross-region variations in inpatient cost of lower extremity amputation among diabetic patients (DLEA) in relation to patient, hospital, and state factors. Methods: Patient and hospital level data were obtained from the 2007 US Agency for Healthcare Research and Quality Healthcare Cost and Utilization Project (HCUP). State level data were obtained from the US Census Bureau and the Kaiser Family Foundation websites. Regression models were implemented to analyze the association between in-patient cost and variables at patient, hospital, and state levels. Results: This study analyzed data on 9066 DLEA hospitalizations from 39 states. The mean cost per in-patient stay was $17, 103. Four out of the five most costly states were located on the East and West coasts (NY and NJ, CA and OR). Age, race, length of stay, level of amputation, in-patient mortality, primary payer, co-morbidities, and type of hospital were significantly correlated with in-patient costs and explained 55.3% of the cost variance. Based on the means of costs unexplained by those factors, the three West coast states had the highest costs, followed by five Midwestern states, and four Southern states, and Kansas were the least costly. Conclusions: Over 40% of the variations in DLEA hospital costs could not be explained by major patient-, hospital-, and state-level variables. Further research is needed to examine whether similar patterns exist for other costly surgical procedures among diabetic patients.